NEW APROACHES TO TEACHING ENGLISH: GIVE THE PUPILS WHAT THEY WANT! - Saidkulova, Mokhinur (Журнал иностранных языков и лингвистики, 2021)
Annotation. This article aims to clarify in what sense there is awareness about using new some technologies, their activities and their applications in language classrooms. The methods are compared with each other in order to reach a general opinion. This article focused on the effects of using techniques applied during English lessons in high methodology style. Keywords: the audio-lingual, communicative approach, task-based approach, large-scale production, evaluation criteria, overarching project, enable student’s communication, smartphones enhance.